MENENTUKAN SISTEM ANTREAN KEDATANGAN YANG OPTIMAL DENGAN MENERAPKAN APLIKASI TEORI ANTREAN PADA PELAYANAN TRANSPORTASI UMUM KERETA API - Erlandi Putra Tri Adira; Paduloh, Zaky Zahran, Raja Akmal Zaidan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The phenomenon of queuing on public transport is a topic that often occurs in public service organizations. Since the implementation of the public transport program by the government, the amount of time required for service users to use public services tends to increase, which can have an impact on the satisfaction and safety of service users. One of the operations research techniques that analyzes queuing problems in production systems or service processes probabilistically is queuing theory. Queues tend to form in public facilities. One of them is the train queue at Bekasi Station. There is a queue between trains waiting to depart and trains departing for the station. This causes the arrival and departure of trains to be delayed from the predetermined schedule, thereby increasing the potential for train passengers. Queuing theory can be used to analyze queuing problems encountered at Bekasi station. Basically, queuing theory is used to determine queuing system parameters such as the average number of arrivals, and service time. These queuing parameters can be used to determine financially optimal system resources. The application of cue theory is growing along with the development of simulation methods and information systems, including system sensitivity analysis